The Influence of the COVID-19 Epidemic on Prevention and Vaccination Behaviors Among Chinese Children and Adolescents: Cross-sectional Online Survey Study - Hou, Zhiyuan; Song, Suhang; Du, Fanxing; Shi, Lu; Zhang, Donglan; Lin, Leesa; Yu, Hongjie (JMIR Publications, 2021)
BackgroundThe COVID-19 epidemic and the related containment strategies may affect parental and pediatric health behaviors. ObjectiveThe goal of this study was to assess the change in children's and adolescents' prevention and vaccination behaviors amid China's COVID-19 epidemic. MethodsWe conducted a cross-sectional online survey in mid-March 2020 using proportional quota sampling in Wuhan (the epidemic epicenter) and Shanghai (a nonepicenter). Data were collected from 1655 parents with children aged 3 to 17 years. Children's and adolescents' prevention behaviors and regular vaccination behaviors before and during the epidemic were assessed. Descriptive analyses were used to investigate respondents' characteristics, public health prevention behaviors, unproven protection behaviors, and vaccination behaviors before and during the COVID-19 epidemic. Univariate analyses were performed to compare differences in outcome measures between cities and family characteristics, using chi-square tests or Fisher exact tests (if expected frequency was <5) and analyses of variance. Multivariate logistic regressions were used to identify the factors and disparities associated with prevention and vaccination behaviors. ResultsParent-reported prevention behaviors increased among children and adolescents during the COVID-19 epidemic compared with those before the epidemic. During the epidemic, 82.2% (638/776) of children or adolescents always wore masks when going out compared with 31.5% (521/1655) before the epidemic; in addition, 25.0% (414/1655) and 79.8% (1321/1655) had increased their frequency and duration of handwashing, respectively, although only 46.9% (776/1655) went out during the epidemic. Meanwhile, 56.1% (928/1655) of the families took unproven remedies against COVID-19. Parent-reported vaccination behaviors showed mixed results, with 74.8% (468/626) delaying scheduled vaccinations and 80.9% (1339/1655) planning to have their children get the influenza vaccination after the epidemic. Regarding socioeconomic status, children and adolescents from larger families and whose parents had lower education levels were less likely to improve prevention behaviors but more likely to take unproven remedies. Girls were less likely than boys to always wear a mask when going out and wash their hands. ConclusionsPrevention behaviors and attitudes toward influenza vaccination have improved during the COVID-19 epidemic. Public health prevention measures should be continuously promoted, particularly among girls, parents with lower education levels, and larger families. Meanwhile, misinformation about COVID-19 remains a serious challenge and needs to be addressed by public health stakeholders.